Superficial Dermal Fillers with Hyaluronic Acid - Bacos, Jonathan T.; Dayan, Steven H. (Facial Plastic Surgery, 2019)
Minimally invasive aesthetic procedures with hyaluronic acid filler have increased drastically since their development in 1989. Patients' desires to avoid surgery and achieve rapid results with minimal recovery led to a transformation in facial plastic surgery, demanding that aesthetic surgeons become proficient in nonsurgical augmentation. Over the years, new hyaluronic acid filler products were developed with different intrinsic properties, allowing clinicians to better treat different deficiencies of the face, reduce postprocedural pain, and optimize outcomes. The purpose of this article is to review the current state of nonsurgical facial plastic surgery with the superficial dermal filler, hyaluronic acid.
Keywords: dermal fillers; hyaluronic acid; esthetics; aging; surgery; plastic